Studi Kritis Atas Narasi Sejarah Khalifah Mu'awiyah bin Abu Sufyan dalam Historiografi Islam - Adib Khairil Musthafa (UIN Sumatera Utara Medan, 2021)
This article aims to provide a critique of the construction of Islamic history writing which almost always provides a negative narrative towards the Muawiyyah ibn Abu Sufyan. In several historical works written by classical and modern historians to orientalist historians and even in several books on Islamic history in Indonesia, Muawiyah ibn Abu Sufyan is almost always described as a leader who is tricky, cunning, cruel, cruel, and ambitious, this article wants to emphasize that writing history in Islamic historiography, especially writing about Muawiyah ibn Abu Sufyan, should not be just accepted as historical fact, let alone writing. history written based on group sentiment, theological flow, ideology to power, its writing will be prone to historical distortion and deceit, therefore this article will try to provide a critique of historical problems and bad narratives about Muawiyah ibn Abu Sufyan and see it from three aspects: methodology, historical construction, and historical writing context. Muawiyah ibn Abu Sufyan's historical construction must be placed as part of the dynamic history of Islamic civilization.